Appendix to ``Regularity of Villadsen algebras'': The failure of the Corona Factorization Property for the Villadsen algebra $\mathcal{V}_∞$ - Bosa, Joan; Christensen, Martin S. (MATHEMATICA SCANDINAVICA, 2018)
In this appendix to M. S. Christensen, “Regularity of Villadsen algebras and characters on their central sequence algebras”, Math. Scand. ?? (????), ???--???, we prove that the Villadsen algebra $\mathcal{V} _∞ $ does not satisfy the Corona Factorization Property (CFP).